Cardiovascular issues in boxing and contact sports - Siegel, S. A. (Clinics in Sports Medicine, 2009)
Despite the inherent risks associated with exercise in general and boxing in particular, the sport has had a limited number of catastrophic cardiovascular events. Screening should be based on risks involved and become more extensive with the advancement of the athlete. Anatomic and electrophysiologic risks need to be assessed and may preclude participation with resultant life style and economic complications. There should be adequate preparation for the rare potential cardiovascular complication at all events, with the ability to rapidly assess and treat arrhythmias.